Phytochemical profiling and antimicrobial activity of ginger (Zingiber officinale) essential oils against important phytopathogens - Abdullahi, A.; Khairulmazmi, A.; Yasmeen, S.; Ismail, I.S.; Norhayu, A.; Sulaiman, M.R.; Ahmed, O.H.; Ismail, M.R. (Elsevier B.V., 2020)
The objectives of this study were to profile ginger essential oils (EOs) phytochemical constituents and antimicrobial activity against important phytopathogens. Ginger EOs was extracted using a modified Clevenger-type apparatus by hydro-distillation then followed by GCMS and headspace analysis of its phytochemical constituents. The phytoconstituents identified were monoterpenes and sesquiterpene hydrocarbons. Food poisoned and disc diffusion techniques were applied to determine the percentage inhibition of fungal mycelial and bacterial growth respectively. The EOs produced mycelial growth inhibition in all the test fungal pathogens after five days of incubation. The MIC and MFC of the EOs on the tested fungi were in the range of 1 μl/ml and 5–6 μl/ml, respectively. The bacterial growth of all the tested isolates was also affected by EOs at 100–500 µl/ml, from weak to strong antibacterial activity. The EOs affected the Xanthomonas oryzae pv. oryzae-strain A isolate most at a higher concentration of 400–500 μl/ml with mean inhibition of 20.66 mm and 22.66 mm respectively, which are found to be effective. The MIC values on the bacterial pathogens were at100 μl/ml. The inhibition zone of positive control (streptomycin) at 15 µg/disc was 25.00 mm and appeared to be efficient. Metabolomics analysis to concurrently quantify variability among multiple compounds in the data sets and identify such compounds responsible for the X. oryzae pv. oryzae-strain-A inhibition were determined. The cross-validated PLS model has shown a strong correlation between ginger EOs and bioactivity. The action of ginger EOs on the cell structure was fully identified using SEM by observing the changes in morphology and integrity of X. oryzae pv. oryzae-strain-A cells. The DMSO treatment (control) showed a normal rod shape cell, while treatment with the ginger EOs showed irregular shape with sunken surfaces, and treatment with antibiotics display abnormal growth of the cells. These findings can, therefore, propose that the ginger EOs could be used as a new antimicrobial agent in suppressing the growth of phytopathogens and as possible new alternatives to synthetic fungicides and bactericides.